Making a grand challenge: the social-symbolic work of conserving nature - Botha, Lindie (Graduate School of Business (GSB), 2022)
Problems like social inequality and shrinking biodiversity seem ever more unwieldy. Scholars are called upon to study how grand challenges like these develop and how organisations respond to them. Scholars and practitioners alike tend to focus on the received and ostensibly objective facts of these challenges, obfuscating the role actors play in socially constructing the very problems they purport to solve. Inspired by calls to better understand the nature of grand challenges and a growing body of research on how actors employ social-symbolic work (SSW) to shape the meaning of complex, contestable phenomena, I ask, how do actors engage in SSW as they grapple with grand challenges, and in doing so, how does SSW shape the tractability of these challenges? I conducted an in-depth, longitudinal ethnographic study of SSW in a state-run conservation agency as actors responded to two interlinked but separate challenges: an acute biodiversity crisis (rhino poaching) in its iconic Kruger National Park, and the slow-burning inequality problem affecting three million people near the park's boundary. Unlike existing studies of SSW that commonly focus on one form of work targeting one social-symbolic object, I find that bundles of SSW targeting imbricated social-symbolic objects - place, identity and temporality - gave challenges meaning. SSW also developed and maintained two distinct ontologies of nature that were compatible with problem framings and solutions, lending legitimacy to actors' novel practices. SSW had a strategic, deliberate outcome, rendering grand challenges into actionable objects accompanied by prescribed sets of solutions that were soon taken for granted. SSW also had an unintended outcome. It reduced grand challenges' tractability. As SSW shaped ontological assumptions and affective repertoires, and suppressed the detection of paradox, actors were dissuaded from finding novel solutions to grand challenges, a critical feature of successful efforts to make them tractable. I contribute to the grand challenges literature by explicating the role of SSW in the construction of not just the challenge itself, but also its tractability. I contribute to the SSW literature by providing an empirical case of actors aligning parallel bundles of work in a single organisation, and I show how this alignment undermines strategic coherence. Finally, whereas much extant work on SSW assumes its explicit, conscious, and purposive character, I point to the subtle, subliminal ways in which work shapes, and is shaped by, actors' moral and emotional dispositions.